Delamination effect on the mechanical behavior of 3D printed polymers (Fracture and Structural Integrity, 2022)
This study aims to assess the delamination effect and predict the evolution of damage in 3D printed specimens to investigate the mechanical behavior occurring due to the delamination of the layers of 3D printed thermoplastic polymers. Thus, additively manufactured ABS samples are subjected to tensile tests Made for different thicknesses of specimens by subtracting layer by layer.The mechanical behavior of the layers and the adherence between the layers are studied in this paper. The deposition of the layers is modeled as a laminated material.The delamination effect on the resistance of printed material is evaluated experimentally by comparing the mechanical characteristics of homogenously printed specimens, and laminated layers gathered together. Thus, the global resistance is reduced significantly due to the lack of adherence.Besides, crack growth, and critical intensity factor investigation are based on damage and rupture mechanics theories.Furthermore, the results allowed us to evaluate the energy behavior of the 3D printed material subjected to static loads and subsequently predict the evolution of the damage and find out the impact of layers' delamination. Indeed, we determined three stages of damage along with the critical life fraction leading to the failure of the specimen.
Keywords: delamination; crack growth; printed polymers; tensile test; damage; ABS